LAPAROSCOPIC LIVING DONOR NEPHRECTOMY: FEASIBILITY AND FIRST EXPERIENCE IN INDONESIA - Mochtar, Chaidir A.; Wahyudi, Irfan; Rasyid, Nur; Rodjani, Arry; Birowo, Ponco; Atmoko, Widi; Satyawan, Yopie Tjandradiguna; Tiera, Hery (Indonesian Journal of Urology, 2012)
Objective: To report our first experience laparoscopic living donor nephrectomy (LLDN). Material & Method: A 37 year-old man was planned for the living-donor transplantation. The recipient was a 63 year-old man sufferingfrom end stage renal disease, and hypertensive heart disease. The donor and recipient were allowed for positive qualification evaluated preoperatively. We applied a transperitoneal approach for the left kidney. Results: The operation time was 300 minutes and the estimated blood loss was 600 mL. The first warm ischemia time was 15 minutes and 24 seconds. There were no major intraoperative and postoperative complications. The donor began oral intake and mobilization within 10 hours and was hospitalized for 4 days. The recipient’s serum creatinine levels reached near baseline levels (1,5 mg/dL) at day 6. Conclusion: LLDN is technically feasible in Indonesia and may increase the rate of kidney donation in Indonesia due to the minimally invasive nature of the procedure.Keywords: Renal transplantation, laparoscopic living donor nephrectomy, Indonesia.